Peculiarities and Differences of French, Uzbek and Russian Fables: Ideology and Image Analysis - Ganiev Fazliddin (Universitas Muhammadiyah Sidoarjo, 2022)
The article provides a comparative analysis of Krylov's tales and their sourcesin the work of J. de La Fonten. “Zarbulmasal”, a collection of popular Uzbek proverbs and fables, willalso be analyzed to analyze the differences between cultures. Krylov's understanding of the Frenchpoet's legacy is studied in two ways: structurally and historically. It shows, firstly, how the plots of LaFonten have changed in Krylov's work, and secondly, how Krylov's approach to the interpretation ofLa Fonten has changed over time. As a result of these analyzes, we can see that the importance ofcultural boundaries disappears in the development of the genre of educational and pedagogicalfables.